Dynamics modelling of a multi body unicycle in three-dimensional space - Aththanayaka, Buddhika Lakmal (Kansas State University, 2022)
Self-balanced unicycle has received the attention of researchers for decades. Over the years, unicycle models with several different assemblies have been introduced by them. A thorough analysis of the dynamics of a unicycle with a frame and a rotating disk is discussed in this research. A torque applied to the rolling wheel maintains the longitudinal stability of the system by moving forward and backward. The rotating disk mounted on the top of the frame maintains the lateral stability of the system by providing a torque. Due to this torque the rolling wheel precess and change its yaw direction. The components of the unicycle assembly are addressed separately for the analysis of the dynamics. First, only the rolling wheel considered. Then, the rolling wheel and the frame are analyzed. Finally, the completed assembly with the rotating disk considered to build the dynamics model. In each of these cases both Newton-Euler and Lagrangian methods are used to obtain the dynamics equations for the unicycle.
Keywords: Unicycle; Newton Euler; Lagrange; Rigidbody dynamics